Frequency of Retinopathy and its Different Grades among Type II Diabetic Patients with Metabolic Syndrome - Rehman, Mohammad Zeeshan Tahir, Mohammad Asghar, Mubashir Rehman, Mohammad Zahid Khan Muhammad Abdur (Pakistan Journal of Ophthalmology, 2014)
Purpose: To determine the frequency of retinopathy and its different grades among type II diabetic patients with metabolic syndrome Material and Methods: This study was conducted in the department of Medicine, Lady Reading Hospital Peshawar from March 2011 to August 2011. Through a Descriptive Cross Sectional Study Design, a total of 201 patients with diabetes mellitus having metabolic syndrome were selected in a consecutive manner from the OPD and fundoscopy was performed to detect and grade diabetic retinopathy and results were recorded. Results: The mean age of patients was 39 ± 12.2 years with 54.7% female and 45.3% male gender. On fundoscopy, diabetic retinopathy was found in 35 (17.4%) of patients with most of the patients with retinopathy lying in older age group i.e. 34.6% in the age group 60+ years and 20% in the age group 50-59 years. On grading of diabetic retinopathy, 40% were in the mild to moderate non proliferative diabetic retinopathy (NPDR) group, 37.1% in the severe non proliferative diabetic retinopathy (NPDR) group and 22.9% were in the proliferative diabetic retinopathy (PDR) group. Conclusion: Diabetic retinopathy is a common sequalae of diabetes in patients with metabolic syndrome with non-proliferative diabetic retinopathy more common than proliferative diabetic retinopathy. It necessitates regular follow up of these patients to prevent development of proliferative disease and its complications. More studies are recommended before making recommendations for modifications in principles of its management. Key Words: Frequency, Metabolic Syndrome, Retinopathy